Contribution of Weather Modification Technology for Forest and Peatland Fire Mitigation in Riau Province - Tukiyat, Tukiyat; Sakya, Andi Eka; Widodo, F. Heru; Fadhillah, Chandra (TDMRC, Universitas Syiah Kuala, 2022)
Peat and forest fire have become an annual disaster and one of which is due to low rainfall. The highest insecurity of forest and peatland fires thus occurs in the dry season, where rainfall is very low, and the intensity of the sun is high. The smoke and carbon emitted result in rising air temperatures and cause global warming. Mitigation and control measures before they happen are necessary. Weather Modification Technology (WMT) serves as one of the technological solutions to control forest fires by increasing rainfall in potentially affected locations. This study aims at examining the level of effectiveness of WMT performance in mitigating forest fires in Riau Province conducted in 2020 measured by rainfall intensity, hotspots decreased, and land water level increased. We used descriptive and inferential statistical approaches using Groundwater Level (GwL) measured data as the parameter for forest and land fire mitigation. The flammable peatland indicator is when the water level is lower than 40 cm below the surface of the peatland. In addition, we also utilized rainfall, surface peat water level, and hotspots. The study was conducted in Riau Province from July 24 October 31, 2020. The results showed that the operation of WMT increased rainfall by 19.4% compared to the historical average in the same period. Rain triggered by WMT contributed to maintaining zero hotspots with a confidence level of 80%. The regression analysis of GwL to rainfall (RF) as depicted by Gwl = - 0.66 + 0.001 RF shows a positive correlation between the two. It thus confirms that WMT can be used as a technology to mitigate forest and land fire disasters.